Vehicle Engine Noise Cancellation Based on a Multi-Channel Fractional-Order Active Noise Control Algorithm - Li, Tao; Wang, Minqi; He, Yuyao; Wang, Ning; Yang, Jun; Ding, Rongjun; Zhao, Kaihui (Machines (Basel), 2022)
For the problem of low-frequency noise suppression in a large area of the vehicle space, this paper proposes a novel multi-channel fractional-order active noise control algorithm and tests its ability for vehicle engine noise cancellation. The algorithm uses fractional-order calculus to replace the integer-order gradient descent to update the weighting coefficients of the filter, thereby avoiding imbalance or over-tuning phenomena during adaptive active noise cancellation and improving the control accuracy of the algorithm. A computer simulation was conducted in the noise cancellation scene of the vehicle, which showed that the algorithm is capable of suppressing single- and mixed-frequency noises, reducing the average sound pressure by approximately 20 dB. The experimental results demonstrated that the algorithm can effectively reduce the peak sound pressure of low-frequency noise for a certain type of vehicle engine by approximately 10 dB, whereas the total sound pressure level is reduced by approximately 4.7 dB.